Full-duplex ku-band phased array antenna using a compact rotman lens beamformer for satellite communications and radar front-end - Figueiredo, Jeann Feitosa (2021)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Mecânica, 2021.